2021
DOI: 10.1002/cncr.33527
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer patients' insurance status and residence zip code correlate with early discontinuation of endocrine therapy: An analysis of the ECOG‐ACRIN TAILORx trial

Abstract: Background Early discontinuation is a substantial barrier to the delivery of endocrine therapies (ETs) and may influence recurrence and survival. The authors investigated the association between early discontinuation of ET and social determinants of health, including insurance coverage and the neighborhood deprivation index (NDI), which was measured on the basis of patients' zip codes, in breast cancer. Methods In this retrospective analysis of a prospective randomized clinical trial (Trial Assigning Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
(63 reference statements)
3
17
2
Order By: Relevance
“…A more recent study found that racial/ethnic disparities in stage IV breast cancer survival were mitigated in areas where Medicaid expansion increased access to care 103 . Studies have also shown that Black women are more likely than White women to experience treatment delay and discontinuation and are less likely to receive guideline‐concordant care, even after controlling for insurance status 104–108 . Efforts to improve survival outcomes among Black women and other underserved populations require multifaceted interventions to address systemic inequalities across the continuum of breast cancer care.…”
Section: Selected Findingsmentioning
confidence: 99%
“…A more recent study found that racial/ethnic disparities in stage IV breast cancer survival were mitigated in areas where Medicaid expansion increased access to care 103 . Studies have also shown that Black women are more likely than White women to experience treatment delay and discontinuation and are less likely to receive guideline‐concordant care, even after controlling for insurance status 104–108 . Efforts to improve survival outcomes among Black women and other underserved populations require multifaceted interventions to address systemic inequalities across the continuum of breast cancer care.…”
Section: Selected Findingsmentioning
confidence: 99%
“…This study by Sadigh et al 1 demonstrates yet again the powerful association between poverty, inadequacy of treatment coverage, and the receipt of poor care and even treatment abandonment. It is an example of the high price paid because of the lack of universal health coverage and social supports to provide adequate health care.…”
mentioning
confidence: 70%
“…Sadigh et al 1 studied patients with breast cancer in the landmark Trial Assigning Individualized Options for Treatment (TAILORx) study and found that social determinants such as a patient's insurance status and neighborhood deprivation index correlate with the patient's adherence to long‐term hormonal therapy. Medicaid and self‐pay patients and patients from the poorest neighborhoods were most likely to discontinue hormonal therapy 1,2 …”
mentioning
confidence: 99%
See 2 more Smart Citations